Dairy industry in Mexico: parameters of the production of milk and supply of the internal market - Loera, Jesús (2017)
Since the beginning of the nineties, milk production in Mexico grew at an average annual rate of 1.3%, occupying the place sixteen in the world dairy production, with 3% of the total. According to SIAP-SAGARPA (2014), the production of bovine milk in 2014 was 11, 108.4 million litres, with a value of 62 million pesos. However, domestic production only contributes to 80% of national consumption, which is why Mexico occupies the world's first place in imports of powdered milk, with 9% of the total. The objective of this research is to analyze the situation of the national dairy industry by identifying and comparing the parameters of the production registered, to have the reference of what to do to increase the productivity and to satisfy the Domestic demand, both of the dairy industry as well as the population. It was concluded that the gap between production and domestic demand for dairy provides an opportunity to increase production in the country and to replace imports. Taking advantage of it, implies strengthening the agro-industrial chain and improving the parameters of the national production, since at the global level Mexico surpassed in 2014 only to Brazil and India in productivity, with scarcely 1.8 tonnes produced per head annually, parameter very Below the 9.93 tonnes produced by head in the United States of America, to whom we buy 9 of every 10 tonnes that we import, and also far below the 9.48 tonnes in Japan and 8.85 in Canada.